PJMHS 2021
DOI: 10.53350/pjmhs2115123218
|View full text |Cite
|
Sign up to set email alerts
|

Perception of the Educational Environment of Post-graduate Residents in Teaching Hospitals across Pakistan

Abstract: Aim: To evaluate the perception of educational environment of post-graduate residents in teaching hospitals of Pakistan. Methodology: This cross-sectional descriptive study was conducted in four tertiary care hospitals in Pakistan from January 2020 to November 2020.The Post-graduate Hospital Education Environment Measure (PHEEM) inventory (40 items on a 0-4 Likert scale) was distributed among 195 post-graduate residents of multiple specialties by convenience non-probability sampling technique. Response was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The Pediatric trainees' overall perception of the educational environment was positive, as observed in the previous studies as well from Pakistan. [12][13][14][15] However, the mean overall and subscale scores were higher in this study compared to the previous local Pediatric studies. [12][13][14] The reason, perhaps, is that the previous studies included trainees from other specialities in addition to Pediatric Medicine trainees.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The Pediatric trainees' overall perception of the educational environment was positive, as observed in the previous studies as well from Pakistan. [12][13][14][15] However, the mean overall and subscale scores were higher in this study compared to the previous local Pediatric studies. [12][13][14] The reason, perhaps, is that the previous studies included trainees from other specialities in addition to Pediatric Medicine trainees.…”
Section: Discussionmentioning
confidence: 77%
“…Most local studies have reported the perception of FCPS trainees. 12 , 13 , 17 , 18 , 21 One of the reasons is that the MD program is a relatively newer phenomenon and that too only in Punjab. The previous MD programs were too few, with very few trainees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 22 studies 6,8,23,[27][28][29][31][32][33]35,[37][38][39]42,[45][46][47][49][50][51][52][53] the mean PHEEM total score was between 81-120, indicating a more positive than negative educational environment, but with room for improvement. In eight studies, carried out in Saudi Arabia 30,43 , Pakistan 24,55 , Ethiopia 34 , Japan 54 , Turkey 25 and Greece 48 , the mean total score was 41-80, indicating an educational environment with many problems. None of the studies showed that the educational environment was considered very bad (score below 40) or excellent (score above 120).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the problems highlighted in the studies were related to social support, with the lack of adequate food during shifts being the main problem in most studies, regardless of the country or region, followed by inadequate accommodation and a culture of blaming the resident. In a study carried out in Morocco 28 , sexual discrimination was considered a problem by half of the residents, associated with racial discrimination, problems also observed in Saudi Arabia 31 , Pakistan 24 and Greece 41 , demonstrating that regional and cultural factors influence the educational environment, especially regarding social support of medical residency programs. In the perception of autonomy subscale, the main negative points were lack of an information manual and clinical protocols for residents, excessive workload, and being called at inappropriate times, while in the teaching subscale, the main problems highlighted were lack of protected time for study and lack of feedback from preceptors.…”
Section: Discussionmentioning
confidence: 99%